Comparative Analysis of Agricultural Incomes from Organic and Conventional Farming Systems in North Benin: Case of the Municipality of Tanguieta - Hountondji, Paul S.; Tovignan, Silvère D.; Hountondji, Ricardo L.; Kokoye, Haroll; Adjiba, Christian S.; Bonouzin, Régina D.; Koussahoue, Stanislas A.; Jonas, Fanyiou (European Scientific Journal, ESJ, 2021)
It is likely that Goals 2, 14, and 15 of the Sustainable Development Goals (SDGs) will never be achieved if organic farming remains economically less profitable than conventional farming. This study was aimed at making a comparative analysis of the economic performance of organic and conventional farming systems. The data were collected from 36 organic and 39 conventional farmers, by individual interviews using semi-structured questionnaires. Descriptive, economic performance indicators and ordinary least square (OLS) regression analysis were used. The results show that the cotton farming activity remains economically more profitable in organic systems, despite the technical constraints of farming. In combination with cotton, corn and soybeans are more profitable in organic systems than conventional. Moreover, level of prosperity, distance from home to cotton farms are positively related to conventional farming system income at 1% and 5% level of significance. Agricultural assets, contact with extension agents, experience in organic farming, secondary activity is positively related to organic system income at 1%, 5%, and 5% level of significance; whilst the household size and the cotton acreage are negatively related to organic system income at 1% and 5% level of significance. It would then be necessary to continue and intensify the programs of diffusion of the best organic cultivation practices to the farmers whatever their experience in organic and to be more interested in corn and soy crops.